Gauge-Singlet Vector-Like Fermion Dark Matter, LHC Diphoton Rate, and Direct Detection - Shrihari Gopalakrishna; Tuhin Subhra Mukherjee (Advances in High Energy Physics)
We study a gauge-singlet vector-like fermion hidden sector dark matter model, in which the communication between the dark matter and the visible standard model sector is via the Higgs-portal scalar-Higgs mixing and also via a hidden sector scalar with loop-level couplings to two gluons and also to two hypercharge gauge bosons induced by a vector-like quark. We find that the Higgs-portal possibility is stringently constrained to be small by the recent LHC di-Higgs search limits, and the loop induced couplings are important to include. In the model parameter space, we present the dark matter relic density, the dark-matter-nucleon direct detection scattering cross section, the LHC diphoton rate from gluon-gluon fusion, and the theoretical upper bounds on the fermion-scalar couplings from perturbative unitarity.